The rookie - Gray, Gordon (Gordon Earl); Ciardi, Mark; Hancock, John Lee; Rich, Mike, 1959-; Quaid, Dennis; Griffiths, Rachel, 1968-; Hernandez, Jay, 1978-; Cox, Brian, 1946-; Walt Disney Pictures; Gran Via Productions ([United States] : Walt Disney Home Entertainment : Distributed by Buena Vista Home Entertainment, 2002)
When a shoulder injury ended his minor league pitching career twelve years ago, Jim Morris resorted to the next best thing: coaching. But Jim's team, knowing their coach is a great ball player, makes a deal with him: if they win the district championship, they want Jim to try out for a major-league organization. Going from worst to first, the team makes it to state, and Jim is forced to live up to his end of the deal. While there prove to be a lot of pitches to be thrown before he makes it off the mound, big-league dreams are revived, and there's no telling where he could go
Videodisc release of the 2002 motion picture
Special features: Audio commentary by Dennis Quaid and director John Lee Hancock ; "The inspirational story of Jim Morris" ; Spring training: tips from the pros ; deleted scenes introduced by the director
Originally released as part of a Blu-ray + DVD combo pack.
Cinematography, John Schwartzman ; editor, Eric L. Beason ; music, Carter Burwell
Dennis Quaid, Rachel Griffiths, Jay Hernandez, Beth Grant, Angus T. Jones, Brian Cox, Rick Gonzalez, Chad Lindberg, Angelo Spizzirri
Closed-captioned
Keywords: Baseball -- Drama; Baseball coaches -- Drama; Feature films